Antimicrobial and antioxidant potential of Streptomyces spp isolated from the rhizosphere of Origanum majorana in Lebanon - Mona Tfaily; Jamilah Borjac (Phytomedicine Plus)
Background: The increasing threat of multidrug-resistant bacteria highlights the critical requirement for the development of new and effective antibiotics from natural sources. Actinobacteria are main producers of natural products to treat various diseases. Purpose: This study aimed to isolate Actinobacteria from the rhizosphere of Origanum majorana, characterize them, and test the antimicrobial activity of their metabolites. Methods: Rhizospheric soil samples surrounding O. majorana plants were collected from 4 locations in Lebanon. The physicochemical characteristics of the soil were studied. Twenty Actinobacteria were chosen for primary screening against different bacterial pathogens using cross streak method and were identified based on morphological and biochemical characteristics. Two Actinobacteria that we coded as WP and OP were chosen for secondary metabolites’ extraction, followed by antibacterial, antioxidant, and hemolysis assessments. These strains were identified using 16S rRNA sequencing. Results: The lowest minimum inhibitory concentration for WP and OP metabolites were 47 and 94 µg/ml respectively against Staphylococcus aureus. WP showed significant biofilm inhibition reaching 95.47 % against S. aureus. WP exhibited similarity with Streptomyces tuirus while OP was similar to Streptomyces sp. OGA5 (99 % and 98 %, respectively). Their metabolites demonstrated time and dose-dependent activities against the tested bacteria. They did not show any haemolytic activity against human erythrocytes even at high concentrations. WP extract exhibited 91.25 % free radicals scavenging activity at 50 mg/ml. Conclusion: The distribution of Actinobacteria is influenced by the physicochemical parameters of soil. S. tuirus produces potent bioactive compounds with promising antibacterial activity making it a valuable source to produce antimicrobial agents.